2018
DOI: 10.1093/gbe/evy062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Footprints of Aquatic Adaptation Including Bone Mass Changes in Cetaceans

Abstract: Cetaceans (whales, dolphins, and porpoises) are a group of specialized mammals that evolved from terrestrial ancestors and are fully adapted to aquatic habitats. Taking advantage of the recently sequenced finless porpoise genome, we conducted comparative analyses of the genomes of seven cetaceans and related terrestrial species to provide insight into the molecular bases of adaptation of these aquatic mammals. Changes in gene sequences were identified in main lineages of cetaceans, offering an evolutionary pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 68 publications
(35 reference statements)
3
15
0
Order By: Relevance
“…Most work has considered cetacean species; pinniped genomes have generally been less available. In strong agreement with the current physiological understanding of antioxidants in both cetaceans and pinnipeds, several genes in the glutathione system – including glutathione reductase, glutathione peroxidases, and γ-glutamylcysteine ligase – are expanded, under positive selection, and/or have amino acid changes in cetaceans (Yim et al, 2014; Zhou et al, 2018). Two peroxiredoxin gene families (PRDX1 and PRDX3) are also expanded in cetacean lineages (Yim et al, 2014; Zhou et al, 2018), suggesting an augmented capacity for redox signaling and antioxidant protection (Perkins et al, 2015).…”
Section: Molecular Underpinnings Of Hypoxia and Oxidative Stress Tolesupporting
confidence: 68%
“…Most work has considered cetacean species; pinniped genomes have generally been less available. In strong agreement with the current physiological understanding of antioxidants in both cetaceans and pinnipeds, several genes in the glutathione system – including glutathione reductase, glutathione peroxidases, and γ-glutamylcysteine ligase – are expanded, under positive selection, and/or have amino acid changes in cetaceans (Yim et al, 2014; Zhou et al, 2018). Two peroxiredoxin gene families (PRDX1 and PRDX3) are also expanded in cetacean lineages (Yim et al, 2014; Zhou et al, 2018), suggesting an augmented capacity for redox signaling and antioxidant protection (Perkins et al, 2015).…”
Section: Molecular Underpinnings Of Hypoxia and Oxidative Stress Tolesupporting
confidence: 68%
“…This raises the probability of an alternative gene family responsible for enhanced oxidative stress resistance or perhaps selection on particular genes responsible for detecting toxicants and activating oxidative defenses, rather than a large gene repertoire. Regarding the former explanation, it has been reported that the peroxiredoxin ( PRDX ) and glutathione peroxidase ( GPX ) gene families have expanded in whale lineages (Yim et al 2014; Zhou et al 2018). On the other hand, it is also possible that the retained GSTs in cetaceans have improved or essential antioxidative properties.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analysis of cetacean genomes has provided important insights into the genomic determinants of cetacean traits and aquatic specializations. Several studies revealed patterns of positive selection in genes with roles in the nervous system, osmoregulation, oxygen transport, blood circulation, or bone microstructure ( 5 7 ). An adaptive increase in myoglobin surface charge likely permitted a high concentration of this oxygen transport and storage protein in cetacean muscles ( 8 ).…”
Section: Introductionmentioning
confidence: 99%